Modifikasi Perbaikan Tanah Dasar Tol Semarang–Demak: Metode Vacuum Preloading dengan Prefabricated Vertical Drain - Deris Faisa Ralindra (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2022)
The Semarang-Demak Toll Road Development Project provides information that conditions in these areas were dominated by rice fields and swamps with high groundwater levels. At STA 21+000 to 22+350, the subgrade was very soft to a depth of 24 m, so subgrade improvement needs to be done to eliminate soil compression. The soil improvement method used was Vacuum Preloading with Prefabricated Vertical Drain. The results of the planning showed that the installation of a vacuum pump at the project site has a pressure of 101.28 kPa. The effectiveness of the pump was 80%, making the vacuum pressure 81.02 kPa or the equivalent of 4.89 meters of soil pile. The square PVD installation pattern with a distance of 100 cm was chosen on the basis of consideration of the consolidation time. This design reduces the time it takes for the soil to reach a 90% degree of consolidation, from 256 years to 16 weeks. The Vacuum Preloading method reduces the heap height, as in STA 21+950. This method also creates a subgrade embankment of only 7,767 m.